Usulan Rancangan Layout Gudang Menggunakan Metode Shared Storage pada PT. XYZ: Proposed Warehouse Layout Design using the Shared Storage Method at PT. XYZ - Ina Ledya; Dene Herwanto; Ardhini Rhisnu Fadylla (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2023)
The company has a raw material warehouse to carry out its production process, but the warehouse needs to be optimized because employees experience limited access to raw materials and the current warehouse layout is still not optimal. This research was conducted to find out the proposed improvements to the raw material warehouse layout so that the company can optimize the function of the existing raw material warehouse within the company. The Shared Storage Method can be used in layout design by arranging storage areas according to the condition of the warehouse floor area. The shared storage method assists in optimizing product storage time so that you can find out when the product will enter and leave the warehouse storage area. The proposals obtained influenced increasing the previous warehouse capacity. There was an increase in capacity of 21.5%. The proposals obtained influenced increasing the previous warehouse capacity. The results of the research on the application of the design for the new layout, at one level, have a warehouse capacity of 33 pallets with ± 14 tons of product. However, by optimizing warehouse capacity by adding one level above it, the warehouse capacity can be doubled, namely 66 pallets with 28 tons of product with product placement between the first and second levels of the same level. The use of warehouse layouts is intended for new image layouts from this study.